Esophagical reparation by antral pediculated graft - Tellechea-Coya, Miguel; Pomatta, Vicente; Giossa, Walter; Curbelo, Elbio; Delgado, Fernando (Cirugía del Uruguay, 1983)
Technical factibility of esophagical reparation by antral pediculated graft in experimental animals as treatment of espophagical stenosis is analized.